PROCEDURAL LEGITIMACY OF CONSUMER ASSOCIATIONS (Perspectivas de las Ciencias Económicas y Jurídicas, 2022)
This work deals with the procedural legitimacy of consumer associations as plaintiffs in a legal claim. To this end, we will first unravel the concept and content of "procedural legitimacy" to then critically assess the current status of the traditional categories related to the protected legal relationship from which the procedural legitimacy starts (subjective right, legitimate interest, simple interest, rights of collective incidence). Once this has been elucidated, we will turn the analysis into the conceptualization of collective advocacy rights and under what conditions and requirements consumer associations can file legal claims in pursuit of the protection of such rights in the field of consumer and user rights.
Keywords: consumers; associations; procedural legitimacy